The bingyun strategy: how subverting armed forces aided the Chinese Communist Party's rise to power - Yang, Zi (2023)
This article explores the evolution and application of the Chinese Communist Party’s (CCP) bingyun strategy pre-1949. Developed by Chinese and Soviet thinkers, bingyun or “Soldier Movement” aimed to subvert opposing armed forces to either bring them under CCP command or cause them to self-destruct. The bingyun strategy was practiced throughout the revolutionary period with lasting legacy in present-day China. By examining cases from the First Kuomintang-CCP United Front, First Phase of the Chinese Civil War, Sino-Japanese War and the Second Phase of the Chinese Civil War, this article demonstrates how bingyun adapted to changing circumstances and its far-reaching consequences for CCP military success that realized its takeover of China in 1949.